Feeling fat in eating disorders: Testing the unique relationships between feeling fat and measures of disordered eating in anorexia nervosa and bulimia nervosa. (June 2018) - Linardon, Jake; Phillipou, Andrea; Castle, David; Newton, Richard; Harrison, Philippa; Cistullo, Leonardo L.; Griffiths, Scott; Hindle, Annemarie; Brennan, Leah
Highlights: Feeling fat in eating disorders is ill-understood. Tested the unique relationships between feeling fat and disordered eating. Feeling fat predicted unique variance in eating restraint and concerns. Feeling fat may be distinct from other components of body image. Abstract: Although widely discussed in theories of eating disorders, the experience of "feeling fat" in this population has received little research attention. This study tested the unique relationships between feeling fat and measures of problematic eating behaviours and attitudes. Data were analysed from individuals with anorexia nervosa (AN; n  = 123) and bulimia nervosa (BN; n  = 51). Correlations revealed considerable unshared variance between feeling fat and shape and weight over-evaluation and depressive symptoms. Moreover, when over-evaluation and depressive symptoms were controlled, feeling fat predicted unique variance in restraint and eating concerns. Findings offer some support for the idea that feeling fat is a distinct and important component of body image concerns in eating disorders. Further research that develops a standardized measure of feeling fat is required. Further research that examines whether feeling fat is an important treatment mechanism is also needed.